Probes for the heterogeneity of muscimol binding sites in rat brain - Müller, Veronika; Ernst, Margot; Baykuchkarova, Aygul; Koniuszewski, Filip; Bampali, Konstantina; Seidel, Thomas; Scholze, Petra (Frontiers in Pharmacology, 2024)
The plant-based alkaloid muscimol is a potent agonist of inhibitory GABAA-neurotransmitterreceptors. GABAA receptors are a heterogenous family of pentameric complexes, with 5 out of 19 subunits assembling around the central anion pore. Muscimol is considered to bind to all receptor subtypes at the orthosteric drug binding site at the β+ and the αinterface. In one of our recent publications, we observed that the antipsychotic drugs clozapine (CLZ), loxapine (LOX) and chlorpromazine (CPZ) although exerting functional inhibition on multiple GABAA receptor subtypes showed diverging results in displacing 3H-mucimol. While a complete displacement could be observed in hippocampal membranes by bicuculline (BIC), and no displacement with CPZ, the compounds CLZ and LOX could only incompletely compete with the radioligand. In addition, the dose-response curves displayed a non-sigmoidal complex form, indicating that they are not following a standard one-site binding pharmacology. In the current study we now aimed to investigate more extensively this heterogeneity of bicuculline sensitive muscimol sites in rat brain. We tested membranes from four different brain regions (hippocampus, cerebellum, thalamus and striatum) and incubated them with 3H-muscimol and the four different compounds BIC, LOX, CLZ and CPZ. We observed a unique pharmacology of each tested compound in the studied brain regions. Combining two of the tested ligands suggests that in striatum all CLZ sites are contained in the pool of LOX sites, while the CPZ sites may in part be non-overlapping with LOX sites. Experiments on recombinantly expressed receptors indicate, that BIC can displace 3H-muscimol from all tested receptors, while LOX and CLZ more potently compete with 3H-muscimol in α4β2 compared to α1β2 or α6β2-containing receptors, suggesting a subtype selectivity. Our experimental findings are supported by docking analysis, designed to find structural correlates of the observed diversity of muscimol sites that are present in the samples from brain tissue and recombinantly expressed GABAA receptor subunit combinations. These findings indicate that 3H-muscimol binding sites in rat brain are more heterogenous than previously thought, with different populations of receptors, which are CPZ, LOX or CLZ sensitive or insensitive. These binding sites show a varying distribution in different rat brain regions.